2011
DOI: 10.2478/v10098-011-0004-x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of selected organochlorine pesticide residues in surface sediments from the Velke Kozmalovce, Ruzin, and Zemplinska Sirava water reservoirs, Slovakia

Abstract: Surface sediment samples from three water reservoirs of Slovakia were analyzed for selected organochlorine pesticides (OCPs). Concentrations of total dichlorodiphenyltrichloroethanes (ΣDDTs) in the sediments from Velke Kozmalovce, Ruzin, and Zemplinska Sirava ranged from 12 to 24 ng g -1 , 5 to 28 ng g -1 , and 1 to 20 ng g -1 , respectively, with the exception of one sediment sample from Zemplinska Sirava, having anomalously high concentration of ΣDDTs (526 ng g -1 ). Concentrations of hexachlorobenzene (HCB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Positive correlation was observed between the mean OCPs in water A samples and the corresponding sediment samples (r = +0.589, p > 0.05). This confirms the role of the sediments as a major sink of pollutants (Doong et al, 2002, Hiller et al, 2011. According to Doong et al (2002), persistency of OCP residues in sediment is possible due to their low solubilities in water and tendency to be adsorbed on suspended particulate matter and benthic sediments.…”
Section: Organochlorine Pesticide Residues In Water and Sediment Samplessupporting
confidence: 64%
“…Positive correlation was observed between the mean OCPs in water A samples and the corresponding sediment samples (r = +0.589, p > 0.05). This confirms the role of the sediments as a major sink of pollutants (Doong et al, 2002, Hiller et al, 2011. According to Doong et al (2002), persistency of OCP residues in sediment is possible due to their low solubilities in water and tendency to be adsorbed on suspended particulate matter and benthic sediments.…”
Section: Organochlorine Pesticide Residues In Water and Sediment Samplessupporting
confidence: 64%
“…The ratio of DDD/DDE can reveal the degradation pathways of DDT, since DDE and DDD are aerobic and anaerobic degradation products of DDT, respectively. A ratio of DDD/DDE less than one (<1) shows aerobic degradation and higher than 1 (>1) shows anaerobic degradation [ 29 , 30 ]. In the fish samples where DDD and DDE were simultaneously detected, the DDD/DDE ratio in the fishes sampled was more than 1 in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, many studies have found Ʃ-DDTs to be the highest in concentration compared to other OCPs measured in freshwater fish with p,p′ DDE the most abundant and persistent of the metabolites analyzed (Wepener et al, 2012;Mzoughi et al, 2016). The studies by Hiller et al (2011) and Mzoughi et al (2016) have shown that p,p'-DDE is resistant against degradation so that it persists in the environment and living organisms. Degradation of p,p′ DDT by the process of mixed-function oxidases to the metabolite p,p′ DDE could be a good explanation for high levels and accumulation of p,p′ DDE in biota (Schmitt et al, 1990).…”
Section: Pesticides Concentrationsmentioning
confidence: 98%
“…Moreover, the ratio of DDD/DDE can reveal the degradation pathways of DDT, since DDE and DDD are aerobic and anaerobic degradation products of DDT, respectively (Aislabie, 1997). A ratio of DDD/DDE less than one (<1) shows aerobic degradation and higher than 1 (>1) shows anaerobic degradation (Hiller et al, 2011). In the present study zooplankton and fish (Clarias gariepinus) samples where DDD and DDE were simultaneously detected, the DDD/DDE ratio in the biota sampled was much less than 1 in all cases.…”
Section: Pesticides Concentrationsmentioning
confidence: 99%